Lateral retention of water droplets on solid surfaces without gravitational effect. (September 2020) - Tang, Sirui; Yao, Chun-Wei; Tadmor, Rafael; Sebastian, Divine
Abstract : Abstract: Gravity is commonly considered negligible when the surface tension is dominant; i.e., the Bond number is less than 1. In this paper, however, the authors present a technique in which drops slide over surfaces with zero effective gravity. Our study compared the sliding motion of water drops on hydrophilic and hydrophobic surfaces in scenarios: one in which effective gravity = 1 (1 g ) and one in which it = 0 (0 g ). The authors found that the lateral retention force was greater under 1 g than it was under 0 g . Also, the results showed that retention forces calculated by Furmidge equation are higher than the measured forces.